Bottom-up strategies for the synthesis of peptide-based polymers. (April 2021) - Martin, Julie; Desfoux, Alexandre; Martinez, Jean; Amblard, Muriel; Mehdi, Ahmad; Vezenkov, Lubomir; Subra, Gilles
Abstract: Thanks to their wide range of biological activities, peptides have been extensively used to afford designed materials with tailored properties. Peptides can be associated to polymers combining the properties of various polymer backbones with those of bioactive peptide sequences. Such conjugates find promising applications in medical devices, tissue engineering, drug targeting and delivery. Improvement of existing polymers by post-modification peptide grafting is achieved through an extensive range of organic reactions, involving the prior preparation of functional polymers displaying suitable anchoring functions. Alternatively, peptides can be used as initiators of polymerization yielding a chimeric molecule bearing a single peptide at the end of macromolecular chains. Finally, novel polymer materials can be designed when the peptide itself is used as a macromonomer. In that case, the unmatched level of repetition of the peptide sequence or/and its self-assembly properties allow to access very high functionalization degree, original structures and bioactivities. Graphical abstract: Image, graphical abstract